Exclusive radiant treatment of C.B.P. "no oat cell" - Musé, Ignacio; Sabini, Graciela; Vassallo, Alberto; Navarrete, Héctor D. (Cirugía del Uruguay, 1982)
The management of patients with lung cancer is cliscussed. The value of palliatíve and radical Rt in this groups is analysed. 567 patients were seen in a period of 10 years (1970-1979). 87 were analysed. The survival rate was 4.5 months, 12% survived 1 year and only 1.1 % survived 2 years. Palliation was obtain in 100% of cases. The following items were studied and related with survival rate: Age, histological type, radiatíon dosage and period in which R t was administrated. This lets us conclude the poor value of Rt in treating lung cancer.